Alliance Formation in Public Private Partnership Housing Projects in Abuja, Nigeria - Dorcas Omolola, Adeagbo; Mohammed, Sani; Sani, Abdulkadir (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The emergence of the Public Private Partnership in housing delivery was to allow the private sector to participate in affordable housing provision. However, the increasing Nigerian population still has a significant shortage of affordable housing units. Hence, the need for an alliance formation approach to provide housing at a cheaper rate is the basic need of man. This study aims to assess the challenges in affordable housing project delivery and examine the factors in alliance formation methods for effective housing project delivery. Research design was used, and the study population was drawn from Architects, Quantity Surveyors, Civil Engineers, Contractors and Project Managers. A purposive sampling approach was adopted for this study. A total of 80 questionnaires were distributed, and 52 were returned. This represents a response rate of 64%. Descritive statistics such as mean and relative important index were used for the analysis of data. The findings show the problem of inaccessibility to land in good locations and inadequate funding by the mortgage system were the significant factors affecting housing delivery. The analysis further revealed that the alliance formation, which involves sharing material and financial resources between public, private, and contractual parties, would significantly contribute to affordable housing delivery.